2020
DOI: 10.1080/1051712x.2020.1787027
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Non-economic Satisfaction as Outcomes of Micro-enterprises’ Perceived Value from Banking Relationships

Abstract: Purpose -The purpose of this paper is to position economic and non-economic satisfaction as outcomes of micro-enterprises' perception of value, and to determine the antecedents of perceived value within the business banking industry.Methodology/Approach -The study is based on a self-administered and internet-based questionnaire conducted in the South African business banking industry. The sample consists of 381 micro-enterprises that employ one or two staff members.Findings -The results reveal that economic sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…The results are also supportive ofZietsman et al (2023) research on micro Enterprise consumers' perception regarding PV in banking services. Their findings indicated that banks could enhance consumers' favourable/positive perceptions regarding SQ and value (PV) if banks would charge fair prices.…”
supporting
confidence: 80%
“…The results are also supportive ofZietsman et al (2023) research on micro Enterprise consumers' perception regarding PV in banking services. Their findings indicated that banks could enhance consumers' favourable/positive perceptions regarding SQ and value (PV) if banks would charge fair prices.…”
supporting
confidence: 80%
“…However, once positive economic satisfaction is secured, parties to the relationship will desire non-economic satisfaction, such as positive relationship quality, the establishment of trust between partners, and open and engaging two-way communication (Glavee-Geo, 2019; Mpinganjira et al, 2017). Zietsman et al (2020a) affirmed the positive relationship between economic and non-economic satisfaction. Therefore, it is hypothesised that:…”
Section: Economic and Non-economic Satisfactionmentioning
confidence: 99%
“…They encompass a variety of more specific constructs, often adapted to specific research contexts, e.g. specific services (banking: Faroughian et al , 2012; Zietsman et al , 2020; engineering: Lapierre et al , 1999), industries (freight forwarding: Gil-Saura et al , 2018) or types of relationship (manufacturer–distributor relationships; Nguyen and Nguyen, 2011).…”
Section: Conceptual and Theoretical Backgroundmentioning
confidence: 99%